Managerial overconfidence: promoter of or obstacle to organizational resilience? - Jennifer Kunz; Lara Sonnenholzner (Review of Managerial Science, 2022)
Organizational resilience provides firms with the capability to face adverse circumstances successfully. Therefore, it constitutes an indispensable capability for each company. As indicated by Upper Echelon Theory, particularly executives and their personal traits exert a major impact on organizational capabilities, decision-making as well as action taking. Thus, they also should play an important role in promoting organizational resilience. However, so far literature lacks a comprehensive understanding regarding these relations. Accordingly, the present paper strives to add to such a comprehensive understanding with a particular focus on managerial overconfidence, one of the most widely and controversially discussed personality trait of executives. To pursue this goal, we develop a model comprising the relevant components of organizational resilience in terms of important resources, conduct a systematic literature review to identify the major corporate areas that are affected by managerial overconfidence and draw conclusions for the identified findings on the relation between organizational resilience and overconfidence. The analysis indicates a positive impact on social resources, a rather negative impact on procedural resources and a mixed impact on financial resources, where e.g. the effect on takeover activities is negative while the impact on financing preferences is at least partly positive. Moreover, the identified literature in large parts provides evidence regarding material resources, while social and procedural resources are covered to a lesser extent, indicating a need for further research.
Keywords: 650; Managerial overconfidence; Resilience; Empirical evidence